Soil–Plant Biochemical Interactions Under Agricultural Byproduct Amendments and Potassium Humate: Enhancing Soil Function and Bioactive Compounds in Sunflower Sprouts - Thidarat Rupngam; Patchimaporn Udomkun; Thirasant Boonupara; Puangrat Kaewlom (Agronomy, 2025)
This study presents an integrated approach to sustainable soil and crop management by evaluating the individual and combined effects of cow manure (CM), rice husk biochar (RHB), and potassium humate (KH)—three underutilized, low-cost organic amendments derived from agricultural byproducts. Uniquely, it investigates how these amendments simultaneously affect soil physical and chemical properties, plant growth, and the accumulation of bioactive compounds in sunflower sprouts, thereby linking soil health to crop nutritional quality. The application of 2% w/w KH alone resulted in the greatest increases in macroaggregation (+0.51), soil pH (from 6.8 to 8.6), and electrical conductivity (+298%). The combination of 1% w/w CM and 2% KH led to the highest increases in soil organic carbon (OC, +62.9%) and soil respiration (+56.4%). Nitrate and available phosphorus (P) peaked with 3% w/w RHB + 2% KH (+120%) and 1% w/w CM + 0.5% KH (+35.5%), respectively. For plant traits, 0.5% w/w KH increased the total leaf area by 61.9%, while 1% w/w CM enhanced shoot and root biomass by 60.8% and 79.0%, respectively. In contrast, 2% w/w KH reduced chlorophyll content (−43.6%). Regarding bioactive compounds, the highest total phenolic content (TPC) was observed with 1% w/w KH (+21.9%), while the strongest DPPH antioxidant activity was found under 1% w/w CM + 1% w/w KH (+72.6%). A correlation analysis revealed that biomass production and secondary metabolite accumulation are shaped by trade-offs arising from resource allocation under stress or nutrient limitations. Potassium, P, soil microbial respiration, and OC emerged as key integrators connecting soil structure, fertility, and plant metabolic responses. Overall, the combination of 1% w/w CM with 0.5–1% w/w KH proved to be the most effective strategy under the tested conditions.